MicroRNA‐16‐5p exacerbates sepsis by upregulating aerobic glycolysis via SIRT3‐SDHA axis - He, Yue‐Xian; Huang, Bo‐Lun; Yang, Yi‐Yu; Song, Wen‐Xiu; Fan, Yong‐Bo; Zhang, Li‐Mei; Liu, Guo‐Sheng (Cell biology international, 2022)
Sepsis is a life‐threatening condition, and treatment for sepsis in clinic is often not available, partially due to insufficient understanding of the pathogenesis of sepsis. Extensive study to elucidate the pathogenesis is required to improve the clinical management and outcome of sepsis. In this study, we investigated the pathogenesis of sepsis using peripheral blood mononuclear cells (PBMCs) from septic patients and studied the underlying mechanism of miR‐16‐5p on aerobic glycolysis in lipopolysaccharide (LPS)‐treated THP1 and Raw264.7 cells. The levels of RNA and protein were determined by real‐time quantitative PCR and immunoblotting assay, respectively. The production of high mobility group box 1 (HMGB1) was measured by enzyme‐linked immunosorbent assay. The levels of succinate and lactate were determined using colorimetric kits. The extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) were measured by extracellular flux analyzer. The results showed that the expression of miR‐16‐5p was elevated, while sirtuin 3 (SIRT3) was decreased in PBMCs from septic patients and LPS‐treated cells, along with accumulation of acetylated succinate dehydrogenase complex, subunit A. Concomitantly, an increase in HMGB1, succinate, lactate, as well as ECAR and a decrease in OCR were observed. Knockdown of miR‐16‐5p upregulated SIRT3 expression, facilitated SDHA deacetylation, and attenuated sepsis‐related aerobic glycolysis. Further study identified that SIRT3 is targeted by miR‐16‐5p, and overexpression of SIRT3 rescued LPS‐induced responses via deacetylation of SDHA. Our findings revealed a novel miR‐16‐5p‐regulated SIRT3‐SDHA axis in sepsis and provided novel insights for sepsis treatment.